Management of Gastrointestinal Tract Diseases by Liver Friendly Drugs: Evaluation of Livelihood Score Efficacy - Md Navim Kabir, Chowdhury (Bangladesh Journal of Medicine, 2023)
Background: Compare efficacy and safety level different Proton pump inhibitors and H2 receptor blockers by livelihood score category. Methods: 52 participants (30 male and 22 female) participated in this cross sectional studies. They were asked about their drug history specially pattern of drug, starting time, change history (if applicable) dosage schedule, relevant adverse effects etc. Results: Out of 52 participants, 27 patients (52%) regularly took proton pump inhibitors for avoiding gastro intestinal irritations more than 7-8 months.10 patients having heart burn and rest of taking different medication for improvement. Out of 27 patients 10 were male and 17 were female. Dependency upon proton pump inhibitors was more in female due to spicy food intake and lack of punctuality of meal. Important clue that 17 patients switch to lansoprazole/rabeprazole from omeprazole/esomeprazole due to insufficient duration of anti-heart burn activity. Condition improved after starting lansoprazole/dexlansoprazole/rabeprazole. Livelihood score of Rabeprazole is D and for lansoprazole/dexlansoprazole it is C. That means hepatic injury is unlikely such as enzyme elevation. Rest of 20 patients who had history of occasional proton pump inhibitor use.Remaining 5 participants didn’t give adequate information about their drug history. After switching, 10 patients found fatty liver grade 1 which previously diagnosed as grade 2. Conclusion: Carbohydrate and protein dominancy in daily food is prime reason for GIT irritation. In advance stage fate may be ulceration as well as non- alcoholic fatty liver disease. Avoiding unnecessary Non-steroidal anti-inflammatory drugs and selection of proton pump inhibitors according to livelihood score, decrease patient’s gastric irritation as well as establishing healthy drug usage. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 224